Impact of Temperature and Depth of Discharge on Commercial Nickel Manganese Oxide and Lithium Iron Phosphate Batteries After Three Years of Aging - Matthieu Dubarry; Andrew Pearson; Keiran Pringle; Youssof Shekibi; Steven Pas (Batteries)
Accurate cell selection is primordial to ensure battery safety and longevity. Unfortunately, because of path dependence, finding out which cells are best adapted to a specific application is not straightforward and might require significant testing. This work provides the analysis of three years of aging, both cycling and calendar, for two batches of commercial cells of different chemistries. Using design of experiments and analysis of variance, this work showed that the impact of temperature and depth of discharge, both at the beginning and end of discharge, are chemistry dependent. Moreover, an analysis of the cells’ degradation modes also showcased different pathways depending on the positive electrode chemistry and the type of aging.